Legal Protection for Victims of Domestic Violence: A Legal and Sociological Perspective - Putri, Ira; Mulyana, Aji; Amalia, Mia (Jurnal Parenting dan Anak, 2024)
A household is a social unit where there is a sense of protection and comfort. In the context of a household, it refers to a husband, wife, and children, as well as people who are related to them by blood, marriage, breastfeeding, nurturing, or guardianship who reside in the household. In addition, people who work to help the household are also seen as family members as long as they live there. An act of violence is a situation where a person commits an act that can cause physical harm, both to themselves and others accompanied by uncontrollable anger and distress. These acts of violence can occur within the household, which can be called Domestic Violence. Domestic violence is an act that harms a person, especially women, which causes suffering physically, sexually, psychologically and / or domestic quarrels both threats in acts, coercion, or unlawful deprivation of independence within the scope of the household. Through this analysis, it is hoped that readers can understand the complexity of the problem of domestic violence and the urgency of preventive measures and stricter law enforcement. The family is the smallest organization in society formed through marriage. A family usually consists of a father, mother and children. However, in many cases, relatives such as parents, husbands or wives, brothers or sisters are also involved.